Development of Mathematics Teaching Materials for Folding, Rotating, and Circumference Symmetry Materials Build Flat - Muizatun Nur Rokhmah; Widya Zidni Khoirun Nisa; Fitrotun Ni’mah; Muh Syauqi Malik; Maslahah (STEAM Journal For Elementary School Education, 2025)
This teaching material is developed based on the demands of the Curriculum by considering the characteristics and needs of grade III MI/SD students, especially in the lower grades who have concrete and visual learning styles. The purpose of this development is to produce teaching materials in the form of magazines that contain materials on folding symmetry, rotational symmetry, and circumference of flat buildings that are presented in a contextual and interesting manner, so as to help students understand the material thoroughly and pleasantly. Teaching materials are designed using three-dimensional images, flat shape cutouts, interactive worksheets, and envelopes containing multiple-choice questions to support students' active engagement during the learning process. The development model used is a 4D model (Four-D Models) which consists of the stages of Define (defining student needs and characteristics), Design (initial product design), Develop (product development and expert validation), and Disseminate (limited dissemination for trials). The subject of development is grade III MI/SD students, with the object of development in the form of an interactive mathematics learning magazine. The research instruments include expert validation sheets, observation guidelines, and student response questionnaires to determine the effectiveness of the teaching materials developed. The findings of the study show that these teaching materials significantly improve students' understanding of the concepts of flat building, especially in terms of active engagement, interest in learning, and ability to solve practice problems. The novelty of this teaching material lies in the three-dimensional and interactive design of the magazine, which has not been developed much before in elementary mathematics learning, as well as the use of multiple-choice question envelopes that give students the space to determine their own learning order.